2011
DOI: 10.1103/physrevlett.107.167403
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Change in the Spin State of Itinerant Correlated Electron Systems

Abstract: Photo-induced spin-state change in itinerant correlated-electron system is studied. The model Hamiltonians before and after photon-pumping are derived from the two-orbital Hubbard model with crystalline field splitting. A photon introduced in the low-spin band insulator induces a bound state of the high-spin state and a photoexcited hole. This bound state brings a characteristic peak in the optical absorption spectra in the photo-excited state. The present results well explain the recent experimental results o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…In an isolated ion, there are the relations U = U + 2J and I = J. The electronic structures in the two-orbital Hubbard model have been investigated so far from the several points of view [25,26,[34][35][36][37][38].…”
Section: Modelmentioning
confidence: 99%
“…In an isolated ion, there are the relations U = U + 2J and I = J. The electronic structures in the two-orbital Hubbard model have been investigated so far from the several points of view [25,26,[34][35][36][37][38].…”
Section: Modelmentioning
confidence: 99%
“…The breakdown depends not only on the field strength but also on the Hubbard-U interaction. Light-induced phenomena in two-orbital models have been studied focusing mainly on quarter-filled Mott insulators using double-exchange models [23][24][25][26][27] . A fieldgenerated high-low spin insulator-ferromagnet transition was observed, as well as bound states, and orbital coherent oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Kanamori et al [12] have calculated the photoexcited state using a two-band Hubbard model and revealed the formation of a high spin polaron bound state by the photoirradiation. Such a bound state brings about the mid--infrared absorption, which might explain the observed enhancement of reflectivity at 0.50 eV.…”
Section: Resultsmentioning
confidence: 99%